Hubungan Pola Asuh Orang Tua Terhadap Minat Baca Siswa Sekolah Dasar - Fironika Kusumadewi, Rida; Permata C, Andarini; Dewi Irianti, Candra (Universitas Muhammadiyah Magelang, 2019)
This reserch aims to find out the correlation of parenting to reading interest g. In this study the researcher uses a simple paradigm research model which only has one independent variable / parental parenting pattern and one dependent variable or dependent yaituminat read students. The indicators used in reading interest in this study were attention, feelings of pleasure, teacher motivation and parents' motivation. This type of research correlates with a quantitative approach that analyzes data with the help of statistical tools in the form of numbers.This research is a correlation research. The approach used in this study is a quantitative approach that analyzes data with the aid of statistical tools in the form of numbers. Samples used students as many as 86 students using simple random sampling method. The sample of this study was tested with SPSS version 23 using correlation regression analysis getting sig results 0.270 indicates that there is a significant relationship in parenting parenting of reading interest but the level of correlation of variable X to variable Y is fairly low. This conclusion is obtained from the interpretation scale table that sig range from 0.200 to sig 0.399 is low, sig <0.199 is classified is lower.